2019
DOI: 10.3390/ani9070400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplementation of Rumen Protected Fats on Rumen Ecology and Digestibility of Nutrients in Sheep

Abstract: Rumen protected fats (RPF) are known to improve animal performance without affecting rumen metabolism in sheep. However, comparative effects of prilled fat, prilled fat with lecithin and calcium soap have not been fully studied. Hence this experiment was planned using 36 male Dorper sheep in a completely randomized design in four treatment groups. The diets included: Basal diet (70:30 concentrate to rice straw) with no added RPF as a control (CON), basal diet plus prilled fat (PF), basal diet plus prilled fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 73 publications
8
35
1
5
Order By: Relevance
“…This study also in line with previous research who also reported the increment population of Ruminococcus albus in Dorper sheep that fed with 5% rumen protected fat diet [11].…”
Section: Effect Of Different Diets On In Vitrorumen Microbial Populationsupporting
confidence: 93%
See 2 more Smart Citations
“…This study also in line with previous research who also reported the increment population of Ruminococcus albus in Dorper sheep that fed with 5% rumen protected fat diet [11].…”
Section: Effect Of Different Diets On In Vitrorumen Microbial Populationsupporting
confidence: 93%
“…Data are the mean of triplicate analyses of each diet. a,b,c Means in the same row with different superscript are signi cantly different (P < 0.05) Table 4 Effect of diet supplemented with concentrate and bypass fat on pH, total volatile fatty acid and methane production from in vitro incubation of Murrah cross and Swamp buffalo rumen uid Diets Breed pH TVFA 1) C2 2) C3 3) C4 4) C2:C3 11 TVFA: Total volatile fatty acids; 2) C2: Acetate ; 3) C3: Propionate; 4) C4: Butyrate; 5) CH 4 : methane production(mM/L); 6) NH 3 : Ammonia; 7) Diet A CON -(100% Brachiaria decumbens); 8) Diet B -(70% Brachiaria decumbens + 30% Concentrate); 9) Diet C -(70% Brachiaria decumbens + 26% Concentrate + 4% Bypass fat); 10) SEM: standard error of means. 11) C2:C3: Acetate:Propionate ratio; 12) ARDC: Apparent rumen degradable carbohydrate; a,b,c,d Means with different superscript letters in the same column are signi cantly different at P < 0.05.…”
Section: Competing Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The depression of NDF digestibility with PW6 could be because it contained the highest UFA concentration ( Table 2). The high proportion of UFA is toxic to rumen microbial populations and particularly to cellulolytic bacteria (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Adding fat up to 6–7% of DM has shown no adverse effects on total tract digestibility ( 126 ). Recent studies have reported no effects of rumen-protected fats on NH 3 -N concentrations, total VFA, and overall bacterial population in sheep ( 127 ). Changes in rumen microbiota ( Acetitomaculum, Lachnospira , and Prevotella ) caused by an increased proportion of concentrates were considerably more significant than fat ( 128 ).…”
Section: Diet–microbe Interactionsmentioning
confidence: 99%